Significant Northward Jump of the Western Pacific Subtropical High: The Interannual Variability and Mechanisms. Issue 6 (14th March 2023) - Wang, Yaning; Hu, Haibo; Ren, Xuejuan; Yang, Xiu‐Qun; Mao, Kefeng
Abstract: The intensity and position of the western Pacific subtropical high (WPSH) have crucial effects on climate and disaster events in East Asia during summer. The WPSH significant northward jump (SNJ) events are the main manifestation of the seasonal evolution of WPSH, which are important for the precipitation over East Asia. Using the daily reanalysis data sets from year 1979 to 2020, this study further defines the early and late SNJ events of WPSH on the interannual timescale, which are connected separately with the tropical, midlatitude subseasonal signals and the local air–sea interaction. However, the mechanisms of the WPSH‐SNJ events are different in the anomalous early and late years. In the early SNJ years, the subseasonal signals from the midlevel East Asia–Pacific teleconnection pattern or the low‐level boreal summer intraseasonal oscillation cause the positive 500 hPa geopotential height anomalies, which contributes to the significant WPSH northward jump in the first pentad of July. However, the above factors are unable to cause the WPSH‐SNJ in the late years. Until the second pentad of August, the collaborative effects between midhigh latitudes wave trains over high levels and cold sea surface temperature (SST) anomalies in the core region lead to the barotropic geopotential height anomalies and the lagged northward jump of WPSH. It seems that the meridional position of WPSH has a complex interannual variability, which is modulated by the solar radiation, the atmospheric disturbances at different levels, and the SST anomalies at the same time. Plain Language Summary: The western Pacific subtropical high (WPSH) is an important component of the East Asian summer monsoon circulation system. The subseasonal northward movement of the WPSH during summer is closely related to the climate of East Asia. However, there are few studies on the interannual variability and the mechanism of the WPSH significant northward jump (SNJ). Focusing on the SNJ events of WPSH, it is found that the time of WPSH‐SNJ exhibits significant interannual variability. After selecting the anomalous early and late northward jump years based on the interannual variability, different mechanisms are revealed. The subseasonal signals in the midlower levels play a vital role in the WPSH‐SNJ in the early years: the circulation anomalies caused by the East Asia/Pacific (EAP) teleconnection pattern or the boreal summer intraseasonal oscillation (BSISO) can affect the meridional position of WPSH and lead to the WPSH‐SNJ. However, the EAP and BSISO signals are ineffective in the late years. The WPSH‐SNJ events are jointly influenced by the upper wave train and the local air–sea interaction. This study will be helpful to understand the process of the northward jump of the WPSH and to improve the skills of subseasonal climate forecasting in East Asia during summer. Key Points: The anomalous early and late years of the western Pacific subtropical high (WPSH) significant northward jump events in 42 years are revealed In the early years, the tropical geopotential height anomalies in the midlower levels determine the time of the WPSH northward jump The upper wave train in the midhigh latitudes and local air–sea interaction control the WPSH northward jump collaboratively in late years